Pengelolaan Daya Tarik Wisata Alam Pantai Duta Yang Berkelanjutan Di Desa Randu Tatah, Kabupaten Probolinggo - -, Jamaludin; Anom, I Putu (Program Studi Pariwisata Program Sarjana, Fakultas Pariwisata, Universitas Udayana, 2023)
This study aims to examine the management of tourist attractions. This study looks at tourism potential in order to determine the sustainability of the Duta Beach attraction in the future. Moreover, this study wants to see the tourist attraction management system in order to update its management which aims to provide efficiency and effectiveness in the management system of tourist attractions. This study uses an exploratory approach. Data collection was conducted through observation, interview, and documentation. The analysis technic uses qualitative methods in displaying data. The finding of this study is the tourism human capital management in Duta Beach is not ready in facing the tourism affairs phenomenon. There is conflict in the management of Duta beach attraction so it needs a solution to create efficiency and effectiveness in its management. Keywords: Tourism attractions management, natural tourism, sustainability